Răspuns :
[tex] \frac{x+5}{4}+ \frac{x+6}{5}+ \frac{x+7}{6}+ \frac{x+8}{7}+ \frac{x+9}{8}=5 [/tex]
[tex] \frac{1}{4}x+ \frac{5}{4}+ \frac{1}{5}x+ \frac{6}{5}+ \frac{1}{6}x+ \frac{7}{6}+ \frac{1}{7}x+ \frac{8}{7}+ \frac{1}{8}x+ \frac{9}{8}=5 [/tex]
[tex](\frac{1}{4}x+ \frac{1}{5}x+\frac{1}{6}x+\frac{1}{7}x+ \frac{1}{8}x)+(\frac{5}{4}+ \frac{6}{5}+ \frac{7}{6}+ \frac{8}{7}+ \frac{9}{8})=5[/tex]
[tex] \frac{743}{840}x+ \frac{4943}{840}=5 [/tex]
[tex]\frac{743}{840}x+ \frac{4943}{840}-\frac{4943}{840}=5-\frac{4943}{840}[/tex]
[tex]\frac{743}{840}x=\frac{-743}{840} [tex]
[tex](\frac{840}{743})* (\frac{743}{840}x)= (\frac{840}{743})*(\frac{-743}{840} )[/tex]
x=−1
[tex] \frac{1}{4}x+ \frac{5}{4}+ \frac{1}{5}x+ \frac{6}{5}+ \frac{1}{6}x+ \frac{7}{6}+ \frac{1}{7}x+ \frac{8}{7}+ \frac{1}{8}x+ \frac{9}{8}=5 [/tex]
[tex](\frac{1}{4}x+ \frac{1}{5}x+\frac{1}{6}x+\frac{1}{7}x+ \frac{1}{8}x)+(\frac{5}{4}+ \frac{6}{5}+ \frac{7}{6}+ \frac{8}{7}+ \frac{9}{8})=5[/tex]
[tex] \frac{743}{840}x+ \frac{4943}{840}=5 [/tex]
[tex]\frac{743}{840}x+ \frac{4943}{840}-\frac{4943}{840}=5-\frac{4943}{840}[/tex]
[tex]\frac{743}{840}x=\frac{-743}{840} [tex]
[tex](\frac{840}{743})* (\frac{743}{840}x)= (\frac{840}{743})*(\frac{-743}{840} )[/tex]
x=−1